2017
DOI: 10.3988/jcn.2017.13.4.325
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Influenza Infection and Vaccination on Exacerbation of Myasthenia Gravis

Abstract: Background and PurposeUpper respiratory infection (URI), including influenza, may exacerbate the symptoms of myasthenia gravis (MG), which is an autoimmune disease that causes muscle weakness. There is also concern that the influenza vaccine may trigger or worsen autoimmune diseases. The objective of this study was to determine the impacts of influenza infection and vaccination on symptom severity in MG patients.MethodsPatients diagnosed with MG were enrolled from 10 university-affiliated hospitals between Mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 17 publications
5
36
0
Order By: Relevance
“…The patient population in this study experienced no adverse effects or exacerbations as a result of vaccines, which is consistent with previous studies on the influenza vaccine . Other studies have shown that an influenza like illness is associated with MG exacerbations leading to higher rates of MG symptom aggravation than the influenza vaccination . In our study, many patients with MG were on immunosuppressive medications at the time of a VPI that preceded an exacerbation.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The patient population in this study experienced no adverse effects or exacerbations as a result of vaccines, which is consistent with previous studies on the influenza vaccine . Other studies have shown that an influenza like illness is associated with MG exacerbations leading to higher rates of MG symptom aggravation than the influenza vaccination . In our study, many patients with MG were on immunosuppressive medications at the time of a VPI that preceded an exacerbation.…”
Section: Discussionsupporting
confidence: 90%
“…6,29 Other studies have shown that an influenza like illness is associated with MG exacerbations leading to higher rates of MG symptom aggravation than the influenza vaccination. 7 In our study, many patients with MG were on immunosuppressive medications at the time of a VPI that preceded an exacerbation. These patients did Further studies are needed to establish vaccination guidelines in MG patients.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Influenza was relatively more common in MG, although our numbers were small, as we only captured patients requiring emergency department or inpatient care. Although theoretical risks of MG disease flare-up exist with annual influenza vaccination, two studies (including one in Ontario) did not find an increased risk of MG exacerbation after influenza vaccination [18,19] and most guidelines recommend in favor of influenza vaccination in patients with MG, particularly those patients with co-existent cardiac or respiratory illnesses [7,20].…”
Section: Discussionmentioning
confidence: 96%